P18 Do bronchial washings improve diagnostic yield in patients undergoing ebus-tbna. (15th November 2016) - Srikanthan, K; Drouot, C; Smyth, C; Giles, T; Walshaw, M; Mohan, K
Abstract : Introduction: EBUS is increasingly used in the diagnosis and staging of lung cancer, particularly where there are no endobronchial lesions. Despite this, in these cases referring physicians often request bronchial washings to be performed at the same time, in the hope of increasing diagnostic yield. We wished to investigate whether this added to the information provided by EBUS-TBNA in such patients. Methods: We looked at all patients who underwent EBUS procedures at our tertiary centre in the last six months, who also had washings taken for cytology at the same sitting where there were no visible endobronchial lesions. We compared the diagnostic yield from EBUS-TBNA with that from the bronchial washings. Results: Of the 111 EBUS patients, 40 underwent concurrent bronchial washings for cytology (mean age 70 years (range 23–89), 23 (58%) male). EBUS-TBNA samples were diagnostic in 39 (98%): 31 malignancy (12 adenocarcinoma, 11 squamous cell carcinoma, 3 small cell carcinoma, 2 carcinoid, 2 breast adenocarcinoma, 1 renal cell carcinoma] and 8 were benign disease. Although bronchial washings were also diagnostic for malignancy in 7 (18%) (4 squamous cell carcinoma, 3 adenocarcinoma), all these cases also had positive EBUS-TBNA samples. There were no cases in which bronchial washings provided the diagnosis in the context of a negative EBUS-TBNA sample. Conclusions: This is the first study to evaluate the effectiveness of bronchial washings in addition to EBUS-TBNA sampling, where there is no visible endobronchial disease. Since each cytological sample analysis costs £75, elimination of bronchial washings in our patients could have saved £3000 over this 6-month period. We conclude that in those patients undergoing EBUS-TBNA, who also have peripheral pulmonary lesions, bronchial washings do not improve the diagnostic yield, and should not constitute routine practice.